Socio-cultural commitment in Things Fall Apart - Adetunji, Bamisile Sunday (Africana Studia, 2020)
The study examines Chinua Achebe’s Things Fall Apart and has the objectives of analysing the socio-cultural commitments as portrayed in the novel. Using the post-colonial and social-cultural perspectives, the study not only focuses on the functions of Achebe as a committed writer who is writing back from an empire to debunk the ignorant and discriminatory assertations of some uninformed European Philosophers on Africans and the black continent, but also examines the theme of clash of cultures, the cultural practices and solidarity of the Igbo people before and during the obnoxious colonial rule. The Ibo/Igbo (Nigerian) society represented in the novel represents African countries confronted by problems of clash of cultures and socio-cultural development. In the novel, the African people lived in peace and harmony and were well organised before the arrival of the colonial masters, and it was their arrival that brought about confusion and disarray to their community. Keywords: Igbo; clash of cultures; Nigeria; Chinua Achebe